CFD analysis during the design of fuel equipment - Robin, M.; Taieb, D (My University, 2017)
Computational Fluid Dynamics (CFD) simulations are increasingly used to apprehend the hydraulic behaviour of fuel equipment in helicopter engines. However, most problematics at stake involve fluid-structure interactions and remain unreachable for traditional mesh-based CFD approaches. The present study investigates the capability of Lattice-Boltzmann methods to cope with the main fluid-structure applications encountered in fuel systems. The first case involves one-way interactions where the pressure generated by a low-pressure pump impeller is modelled. The second case study covers two-way interactions where the dynamic coupling between a deltaP constant poppet, subjected to pressure loads and a spring force, and a controlled metering valve is computed. In the last case, instabilities of a check valve are reproduced and oscillations eigenfrequencies are correlated with experimental data. XFlow Latice-Boltzmann solver shows good capability to handle all of those complex applications. Obtained results and reference data are in very good agreement with a significant improvement in computational time. Those methods open new perspectives to deal with a large panel of fuel system problematics like gear pumps or fire test scenarii.